Water footprint analysis to improve water use efficiency in table grape (Vitis vinifera L. cv. Crimson seedless) production. A South African case study - Kangueehi, Grace Nandesora (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.